Malaysia your profit centre in Asia - Lembaga Kemajuan Perindustrian Malaysia (Kuala Lumpur : Malaysian Industrial Development Authorithy, 2004)
Malaysia has unveiled an ambitious plan through the Economic Transformation Programme (ETP) to propel the country towards becoming a high income and developed country by 2020. The Malaysian Government has also unveiled the 10th Malaysia Plan 2011 - 2015 and the 12 National Key Economic Areas (NKEAs) under the ETP.
Keywords: Budget -- Malaysia